Tiket Padalubhasaan and Audio-Assisted Reading: Innovative Cultivation of Reading and Comprehension Skills of Twelfth Grade Students - Arturo A. Roda Jr. (East Asian Journal of Multidisciplinary Research, 2023)
This study aimed to cultivate the reading skill, comprehension, and fluency of the twelfth-grade students. Quantitative research and quasi-experimental methods were used with a research design of one group pre-test-post-test. Philippine Informal Reading Inventory was used to evaluate students' reading skills, comprehension, and fluency. The collected data were subjected to analysis through mean, t-test, and Glass Delta. It can be said that the study was successful because the reading skill level of all the students went from the previous level of Frustration to Instructional. The students' skills also increased in the aspects of reading speed, comprehension, and fluency. Also, data analysis showed that there was a significant difference in the students' score in the pre-test and post-test after applying the intervention.